2008
DOI: 10.1186/1471-2164-9-343
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate regulated genes and their wide involvement in the Lactococcus lactis stress responses

Abstract: Background: The development of transcriptomic tools has allowed exhaustive description of stress responses. These responses always superimpose a general response associated to growth rate decrease and a specific one corresponding to the stress. The exclusive growth rate response can be achieved through chemostat cultivation, enabling all parameters to remain constant except the growth rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
56
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 35 publications
8
56
0
1
Order By: Relevance
“…It is intriguing to speculate that the intrachromosomal heterogeneity of the periodic signal and associated DNA curvature could play a role in regulation of gene expression. It has been known that chromosomal location of genes in prokaryotes is not random, but the nonrandomness has been generally ascribed to locations relative to the origin and terminus of replication, colocalization of coexpressed genes, or evolutionary constraints related to lateral gene transfer or gene amplification (6,8,15,25,31,32). We propose that heterogeneity of physical structure of the nucleoid reflected in the intrachromosomal variance of sequence periodicity can serve as an additional constraint on gene location, possibly by modulating the gene expression in different chromosomal regions.…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing to speculate that the intrachromosomal heterogeneity of the periodic signal and associated DNA curvature could play a role in regulation of gene expression. It has been known that chromosomal location of genes in prokaryotes is not random, but the nonrandomness has been generally ascribed to locations relative to the origin and terminus of replication, colocalization of coexpressed genes, or evolutionary constraints related to lateral gene transfer or gene amplification (6,8,15,25,31,32). We propose that heterogeneity of physical structure of the nucleoid reflected in the intrachromosomal variance of sequence periodicity can serve as an additional constraint on gene location, possibly by modulating the gene expression in different chromosomal regions.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that in C. crescentus spoT is required for expression of cspD, either via a direct effect of ppGpp on its transcription or indirectly by the effects on the overall cell response to carbon starvation and growth. In a global analysis of Lactobacillus lactis gene expression in response to carbon limitation (isoleucine or glucose starvation), the stringent response and growth rate were compared, and the results showed that the stringent response is not the general mechanism controlling growth rate modifications or glucose starvation (11).…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization signals were quantified and statistically treated as previously described (10,34,35). Briefly, the local background was removed, and signals were normalized by the mean intensity of the corresponding membrane.…”
Section: Methodsmentioning
confidence: 99%